THE FACTORS AFFECTING INCREASED BLOOD PRESSURE IN HYPERTENSION PATIENTS IN THE ERA OF THE COVID-19 PANDEMIC IN PATAI GEMI VILLAGE 2022 - dedi dedi; Haryanto Haryanto; Syahrizal Syahrizal (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2022)
Background: Hypertension is a non-communicable disease that is still a health problem in Indonesia. Hypertension is one of the comorbidities that increase the risk of contracting Covid-19 disease. Hypertension is a condition of abnormally high blood pressure that is showed by systolic blood pressure of more than 140 mmHg and diastolic was more than 90 mmHg. Objective: This study aimed to determine the influence factors on the occurrence of blood pressure increase in patients with hypertension in the COVID-19 pandemic era at Pantai Gemi Village. Methods: This is quantitative research with a descriptive correlation design and uses a cross-sectional approach. The sample used in this study was 79 respondents who suffered from hypertension taken by total sampling technique. The instrument of this study was by questionnaire about factors related to the incidence of hypertension. The analytical method using Kendall tau. Results: There was a relationship between the consumption of salty food 0.000, family history of 0.002, saturated fat consumption of 0.001, exercise habits of 0.003, and the most dominant factors influencing the incidence of hypertension in Pantai Gemi Village showed a significant value of 0.000 and a t-value of 4.887. Conclusion: It can be concluded that there is a relationship between food consumption such as saturated food with family history and there is no relationship between genders, body mass index (BMI) with the occurrence of hypertension at Pantai Gemi Village. Keywords: Hypertension Incidence, Salty Food, Saturated Fat, and Family History